Causal theory on acceleration of seed germination in the vicinity of high voltage direct current transmission line. (21st December 2021) - Kumar, Abhimanyu; Pandey, Om Prakash
Graphical abstract: Highlights: Seed germination is known to be influenced by electric/magnetic field. The paper provides a theoretical framework for the same. This allows a causal explanation for the effect of HVDC lines. The current variation due to effect of electrical loading has been discussed too. Thus, this work opens new avenues of research in this field. Abstract: Seed germination is the primary stage of growth in a seed. A wealth of experiments exist in literature to support the existence of correlation between seed germination to the electric and magnetic fields. This becomes more important as researchers have suggested to develop technologies to build ecologically clean and environment-friendly solutions to agricultural practices. Although the literature supports the existence of seed germination acceleration, the lack of a definite causal theory has been observed by numerous researchers over decades. After considering all the existing experimental data, we have formulated a causal theory to explain the factors influencing seed germination around high voltage DC transmission lines. This work opens new avenues of research in this field.